Variables influencing the in vitro measurement of spontaneous aggregation of human platelets - Ghali, Claudia; Fioretti, Antonella; Scavone, Mariangela; Bossi, Elena; Clerici, Bianca; Birocchi, Simone; Popov, Evgeny; Centola, Marco; Podda, Gianmarco; Cattaneo, Marco (Haematologica (Roma), 2025)
Not available.Not available.